An Assessment of Adherence to Exclusive Breast-Feeding among Student Mothers at the University of Cape-Coast - Sarkodie, Noble Amoako (Pakistan Journal of Nutrition, 2014)
The study was carried to investigate the extent of adherence of exclusive breast-feeding among student mothers in the University of Cape Coast. The research assessed perceptions of student mothers in this regard. Stratified, proportionate sampling method was used to select student mothers who were lactating or had weaned their babies in the past 3-6 months of this study. Questionnaires were administered to collect data from the respondents. Frequency distribution tables and discussions were used to sum up the data. The study revealed that all the respondents (100%) were aware of the six months exclusive breast feeding but only four percent of the respondents were able to breast-feed exclusively. The study recommend that, there should be a conscious effort by women’s groups and policy makers to ensure that time table schedules in tertiary institutions will enable student lactating mothers to breast-feed their babies for the benefit of mothers and babies concerned.